Uji Efektifitas Daya Hambat Sabun Cair Cuci Tangan di Kota Surabaya Terhadap Pertumbuhan Bakteri Staphylococcus aureus dan Escherechia Coli secara in Vitro - Purbosari, Ira (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Currently, the rise of the corona disease (Covid-19) has become a worldwide pandemic which has been declared by Who to be the center of attention around the world. One of the prevention efforts is to wear a mask and wash hands. Hand washing is done by using liquid soap and rinsing with soapy water. The degree of acidity (pH) of soap serves to inhibit the growth rate and kill bacteria. This research is to see the antibacterial activity of unbranded and branded liquid soap products and have distribution permits that are traded freely in the marketplace. Using the disc diffusion technique method, the zone of inhibition is determined. In this study, a positive control was used, namely liquid soap that already had a distribution permit and a negative control in the form of aquadest. The test results obtained that the diameter of the inhibition zone for liquid soap, namely S. aureus in liquid soap, was 27.7 mm and in positive control was 24.9 mm. Meanwhile, in E.coli, the average diameter of the inhibition area in liquid soap was 29.3 mm and in positive control was 32.8 mm. This is influenced by the concentration of antiseptic, soap composition, antibacterial, and pH of the soap, as well as bacterial cell wall components and dilution. And from the results of statistical analysis using the Tukey test method, it was found that there was a significant difference in liquid soap (p-value 0.000) which was significant in inhibiting the rate of bacterial growth.Keywords: bacterial growth, escherichia coli, hand washing, inhibition test, liquid soap, staphylococcus aureus